Turning Crisis into Opportunity: Unfolding Ukraine’s Trade Potential with the Canada-Ukraine Free Trade Agreement - Bogdanova, Iryna (East/West, 2021)
To offset the devastating effects of the trade war waged by the Russian Federation, Ukraine has undertaken laudable efforts since 2014 to negotiate new trade agreements with other states. Against this background, the negotiations of the Canada-Ukraine Free Trade Agreement were finalized and the agreement came into force on 1 August 2017. This article explores the positive impact of this agreement on bilateral trade flow between the states and describes its potential contribution to unfolding Ukraine’s trade potential.